Restricting dry matter intake of stocker calves and its subsequent effects on grazing, feedlot performance, and carcass characteristics - Anglin, Chad O'Neal (Kansas State University, 2008)
An experiment was conducted to evaluate the effects of dry matter intake (DMI) restriction on early receiving performance by steers in a drylot and subsequent grazing performance, feedlot performance, and carcass characteristics. During the backgrounding period, crossbred, weanling steers (n = 329; initial BW = 191± 5.52 kg ) were randomly assigned to 1 of 4 DMI levels corresponding to ad libitum, 2.50% of BW (2.50%), 2.25% of BW (2.25%), and 2.00% of BW (2.00%) for 62 d. During the subsequent grazing period, the same steers were randomly assigned to 13 paddocks to graze for 90 d. Paddocks were stocked at 281 kg live weight per hectare. Initial steer BW were similar on each pasture and each backgrounding treatment was equally represented within a paddock. During the feedlot period, steers were finished at a commercial feedlot and were assigned to 1 of 4 pens according to their rank in BW. Entire pens were harvested when average steer BW reached 545 kg. During the backgrounding period, ad libitum-fed steers had greater (P < 0.001) ADG and final BW than other treatments; steers fed at 2.50 and 2.25% of BW had similar ADG and final BW and were greater (P < 0.001) than steers fed 2.00% of BW. During the grazing period, compensatory gain was observed in restricted DMI treatments. Steers fed at 2.00% of BW had greater (P = 0.006) ADG than ad libitum-fed steers but an ADG similar to that of the other restricted DMI treatments. Steers fed ad libitum, 2.50% of BW, and 2.25% of BW had similar final BW and steers fed 2.00% of BW had lesser (P < 0.001) final BW than other treatments. During the feedlot phase, steers fed 2.00% of BW were on feed longer (P < 0.05) than other treatments. Growth compensation during grazing illustrated that restricted feeding immediately prior to pasture grazing can reduce backgrounding costs.
Keywords: backgrounding; compensatory gain; grazing; limit-feeding; steers; Agriculture, Animal Culture and Nutrition (0475); Agriculture, Range Management (0777)